Personal autonomy and pluralism of values in the liberalism of Joseph Raz - Toscano Méndez, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
This paper wants to pay tribute to Joseph Raz, who died on May 2, one of the great contemporary philosophers, whose work covers all domains of practical philosophy. Here I will focus on his political philosophy to expose how Raz understands the moral core of liberalism, namely, the moral principles that justify the doctrine of limited government. I will explain first that Raz rejected the label of ‹‹perfectionist liberalism››, under which his version of liberalism is usually discussed. I will then consider the theory of value pluralism as well as the ideal of personal autonomy, since they constitute the basic moral principles of his conception of liberalism. Finally, I will examine the relationship between autonomy and value pluralism, since there are important misunderstandings about it, and I will offer an alternative interpretation of the value of autonomy using the strong version of value pluralism.